PERAN MODEL ABC DALAM MEMETAKAN KECEMASAN SOSIAL DAN KETERGANTUNGAN YANG DIPICU OLEH MEDIA SOSIAL PADA GEN-Z DENGAN MENGGUNAKAN PENGKONDISIAN KLASIK - Ildagis Binarsia; Fahmida Qurrotussalwa; Muhamad Afifuddin Ghozali (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
Social anxiety and social media addiction often form a cycle in which individuals avoid direct interaction due to anxiety, but seek validation through social media, which actually exacerbates social anxiety due to the pressure to appear perfect. Based on information obtained from the counselee, the influencing factor is that the counselee needs validation and is dependent on her confidence through social media. The purpose of this scientific journal is to find out the role of the ABC model in flattening social anxiety and social media dependence in Gen-Z. The method used in this scientific journal is deductive qualitative with a case study approach. The research subject is an adolescent gen-z who has the potential to exhibit self-protective behaviours due to excessive anxiety and social media addiction that affect self-confidence. Data was collected through one-to-one counselling with the consent of the counselee. This scientific journal found two themes, namely social anxiety and social media addiction. The ABC model helps to map and overcome social anxiety and social media addiction in Gen-Z, which is influenced by the need for validation and low self-confidence.